The Development Of React Strategy-Oriented Learning Media on Specialization Mathematics For 12th-Grade SMAN 1 Kembangbahu - Dhini Marliyanti; Marianus Subandowo; Hary Karyono (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The occurring digitalization of education due to the Covid-19 pandemic is an unavoidable situation.The aims this study was to develop REACT strategy-oriented learning media on specialization mathematics for 12th-grade. This study used the 4D development model (Define, Design, Develop, Disseminate). The data collection instrument is a questionnaire form that was distributed to material experts, learning design experts, media experts, and respondents. Respondents for individual, small group, and field trials were 12th-grade students of SMAN 1 Kembangbahu. The results of the feasibility test of learning media got percentages of 83%, 89%, and 93% from material experts, learning design experts, and media experts. The results from individual trials are 91%, from small group trials 88%, and from field trials are 90%. Based on the results of the validation, the interactive REACT-oriented Google Sites learning media on Specialization Mathematics for 12th-grade students of SMAN 1 Kembangbahu concluded as feasible for use as specialization mathematics learning media with an average percentage of 90%.